Faktor – Faktor Terkait Tingkat Keparahan Infeksi Coronavirus Disease 2019 (COVID-19): Sebuah Kajian Literatur - Abiyyu Didar Haq; Adli Putra Nugraha; I Komang Gede Andhika Wibisana; Febbi Anggy; Fiana Damayanti; R.R. Ditya Mutiara Syifa; Ni Putu Visty Widhiani; Cut Warnaini (JIMKI: Jurnal Ilmiah Mahasiswa Kedokteran Indonesia, 2021)
Background: COVID-19 pandemic that started in the early 2020 triggers the declaration of Public Health Emergency of International Concern (PHEIC) by WHO. Caused by SARS-CoV-2 virus, COVID-19 mainly infects the respiratory tract by binding to the ACE2 receptor. COVID-19 infection can cause many clinical manifestation from no symptom to severe life-threatening symptom depending on many factors. Factors that can determine the severity of clinical manifestation is urgently needed to be recognized by our clinician in order to be able to anticipate patient’s condition before the severe clinical manifestation even begins. This literature review is aimed to summarize and discuss some factors that are most often showed up and determined the severity of COVID-19 infection. Methods: This literature review uses journal article that are sourced from online databases such as PubMed and Google Scholar. The type of article that will be chosen are research article, systematic review and meta-analysis, narrative review, and literature review with the topic of transmission, clinical manifestasion, pathogenesis, immune response, and severity risk factor of COVID-19. Discussion: From our literature search, it is concluded that the factors that are most likely to determine the severity of COVID-19 infection is age, comorbid disease, vitamin D deficiency, and obesity. These four factors are not four independent factors but rather overlapping and interconnecting factors that determines the severity of COVID-19 infection. Conclusion: Most of the factors that determined the severity of COVID-19 mainly are easily preventable factors. Therefore, the knowledge and awareness of our clinician about these factors will really helps anticipating the severe clinical manifestation among COVID-19 patients before the manifestation even starts to appear.